A rubric for pre-service teachers to evaluate meaningful physical education - Cañabate, Dolors; Bubnys, Remigijus; Hernández, Esther; Colomer, Jordi (Frontiers in Education, 2024)
This manuscript presents the definition, implementation, and validation of a new rubric for assessing and improving meaningful physical education activities in tertiary education: The Rubric for Meaningful Physical Education Assessment (MEANPE). We present the rubric's validation based on twelve international external experts' appraisals, and on the perception of 250+ pre-service teachers (PST). The manuscript presents the validity, correspondence, formulation and appropriateness of the indicators and their levels. We found that there are statistically significant differences in student scores between the pre-and post-implementation, suggesting that the MEANPE rubric is a valid and reliable instrument with which to assess meaningful physical activities in primary school classes.